Cinema 4D Dalam Pipeline Produksi Serial Animasi - Ardiyansah Ardiyansah (Bina Nusantara University, 2011)
Cinema 4D is best known as software that is efficient in render time. This is very beneficial especially for those who engaged in animated projects with tight deadlines and require work time efficiency, such as serial project. In addition to time, in the animated series production pipeline also generally require various items of work that involves a lot of resources implemented in parallel. This is to avoid delays to the overall project progress whenever a work item suffers setback due to any reason. Cinema 4D as a tool, allowing a project carried out with the most efficient method in accordance with needs, and flexibility that is the appeal of Cinema 4D as well as strength in the context of the animated series production.